HUBUNGAN KUALITAS TIDUR DAN POLA MAKAN DENGAN TIMBULNYA ACNE VULGARIS PADA REMAJA - Indrayani, Ni Luh Sri; Prihandini, Claudia Wuri; Triana, Komang Yogi; Wardana, Gede Harsa (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Acne vulgaris affects many adolescents and can have long-term consequences, including the formation of permanent scars. Acne vulgaris is a multifactorial condition, one of which is caused by poor sleep quality and an unbalanced diet. This study aims to investigate the relationship between sleep quality and dietary patterns with the onset of acne vulgaris in adolescents at MMC Mambal Clinic. The study was conducted using a quantitative design with an analytical observational approach and a cross-sectional design, carried out in April 2025 with a sample size of 53 respondents selected using consecutive sampling technique. Data were collected using the St. Mary’s Hospital Sleep Questionnaire, a dietary questionnaire, and the Lehman’s Grading System for measuring acne vulgaris. Data were analyzed using Spearman’s rho test with p<0.05. The results showed that the majority of participants had good sleep quality (66%) and good dietary patterns (64.2%), with the majority experiencing mild acne vulgaris (64.2%). There was a significant association between sleep quality and the occurrence of acne vulgaris in adolescents at MMC Mambal Clinic with a p-value <0.032, and there was a significant association between dietary patterns and the occurrence of acne vulgaris in adolescents at MMC Mambal Clinic with a p-value <0.012. The recommendations from this study are expected to motivate adolescents to regularly monitor their dietary patterns and sleep quality to prevent the occurrence of acne vulgaris.